2004
DOI: 10.1523/jneurosci.1302-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Plasticity of Postsynaptic Kainate Receptors in Hippocampal CA3 Pyramidal Neurons

Abstract: Kainate receptor-mediated components of postsynaptic currents at hippocampal mossy fiber synapses have markedly slower kinetics than currents arising from AMPA receptors. Here, we demonstrate that other aspects of kainate and AMPA receptor function at this synapse are distinct; in particular, kainate receptor currents are less sensitive to short-and long-term increases in presynaptic strength. EPSCs arising predominantly from AMPA receptors exhibited well characterized paired-pulse facilitation, frequency faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…Thus, at this membrane potential in the presence of GYKI 53655, Mf-EPSCs are in great part mediated by KARs. In response to a train of five pulses at 20 Hz, the amplitude of KAREPSCs during the train increased and remained potentiated 500 ms after the train because of presynaptic facilitation (Salin et al, 1996;Ito et al, 2004) (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, at this membrane potential in the presence of GYKI 53655, Mf-EPSCs are in great part mediated by KARs. In response to a train of five pulses at 20 Hz, the amplitude of KAREPSCs during the train increased and remained potentiated 500 ms after the train because of presynaptic facilitation (Salin et al, 1996;Ito et al, 2004) (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, short-term depression of KAR-EPSCs in conditions of high afferent activity leading to spike discharge is expected to exert a feedback inhibition on the sustained depolarization induced by KAR-EPSPs. Interestingly, it was reported that KAR-EPSCs show attenuated forms of presynaptic plasticity compared with AMPAR-EPSCs (Ito et al, 2004). Both mechanisms will concur in preventing the overactivation of synaptic KARs under conditions of sustained network activity and might thus favor information processing in conditions of short bursts of afferent stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horizontal hippocampal slices (0.35 m) were made from P30 to P40 129SvEv mice as described previously (Ito et al, 2004). Whole cell patch-clamp recordings of AMPA-excitatory postsynaptic currents (AMPA-EPSCs) were made from CA1 pyramidal cells while stimulating Schaffer collateral inputs with a monopolar glass electrode in the stratum radiatum.…”
Section: Methodsmentioning
confidence: 99%
“…Recent electrophysiological studies using rat brain preparations, however, have shown that taurine application induced long-lasting synaptic potentiation [3,6]. The features of this taurine-induced synaptic potentiation are similar to those of long-term potentiation (LTP) [4,19], which is a typical example of synaptic plasticity, and is thought to be a basic model for learning and memory [8], indicating that taurine is likely to be involved in learning and memory. Despite accumulation of findings on the relationship between taurine and synaptic plasticity by electrophysiological studies, the effect of taurine on learning and memory at the behavior level is complicated.…”
mentioning
confidence: 93%